EXPERIMENTAL INVESTIGATION OF CRITICAL HEAT FLUX IN ANNULUS AT LOW PRESSURE AND LOW FLOW PARAMETERS - Daniel Vlček; Ladislav Suk; Kamil Števanka; Taron Petrosyan (Acta Polytechnica CTU Proceedings, 2020)
Steady state flow boiling experiments were conducted on a technically smooth Inconel 625 tube with outer diameter 9.1 mm at inlet pressures 131, 220 and 323 kPa, inlet temperatures 62, 78 and 94 °C and approximately 400, 600 and 1000 kg/(m2.s) mass flow. Water of these parameters was entering into the vertically aligned annulus, where the uniformly heated tube was placed until the critical heat flux (CHF) appeared. The experimental data were compared to estimations of CHF by local PGT tube correlation and Groeneveld’s look-up tables for tubes. The results imply that in the region of low pressure and low mass flux, the differences between calculations and experiments are substantial (more than 50 % of CHF). The calculations further imply that look-up tables and tube correlations should be corrected to the annulus geometry. Here, the Doerffer’s approach was chosen and led to a substantial enhancement of CHF estimation. Yet, a new correlation for the region of low pressure and flow is needed.